The Influence Of The Rupiah Exchange Rate, Inflation And Interest Rates On Investment Returns On Islamic Life Insurance Companies In Indonesia Stock Exchange For The 2018-2020 Period - Anton Priyo Nugroho; Ardiani Ika Sulistyawati; Nirsetyo Wahdi; Arief Himmawan Dwi Nugroho; Emaya Kurniawati (Yayasan Riset dan Pengembangan Intelektual, 2023)
Investment opportunities greatly determine the company value based on formed share prices. Growth of capital is often observed by the indicator of the market Stock Price Index. Stock Price Index fluctuation is significant to determine whether investors will sell, hold, or buy more shares. This study aims to analyze and examine the factors influencing the exchange rate, inflation and interest rates on return investment in the Sharia Life Insurance Companies in the period 2018-2020. The method of research is using the quantitative and regression analysis. The sample is the Sharia Life Insurance Companies which are consistenly publish financial reports for the 2018-2020 period listed on the Indonesia Stock Exchange with a total sample of 52 companies. The sampling technique is non-probability sampling with saturated sampling method. The data was analyzed with IBM SPSS version 21 and was carried out by several tests such as validity test, reliability test, classic assumption test, linear regression analysis and coefficient of determination test. The results of this study indicate that the exchange rate, inflation and interest rates simultaneously and significantly influence on investment returns. The results of the partial test demonstrates that the exchange rate, inflation and interest rates have a significant but negative effect on return investment. If the exchange rate increases, investors will not be interested in holding their shares. It causes the investor not interested to switch their portfolio into deposit because of the low interest rate and the declining trend of inflation, which caused inflation does not have significant effect on return.